Revitalisasi Nilai Lokal: Model Proyek Partisipatif Berbasis Budaya Cianjur dalam Pembelajaran Pancasila - Indriyani, Dina; Naidu, Noor Banu Binti Mahadir (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
There is a need for an instructional model in Pancasila Education that can effectively transmit the values of local wisdom embedded in the Pilar Budaya Cianjur (Cianjur Cultural Pillars), as part of Indonesia’s national cultural heritage. Therefore, this study presents a suitable learning model for conveying these local wisdom values so that they can be institutionalized in the lives of younger generations. This research is a development study, employing data collection techniques such as interviews, literature review, focus group discussions (FGDs), and experimentation. The findings reveal that the Participatory Project-Based Learning Model is effective in transforming the local wisdom values of Pilar Budaya Cianjur within Pancasila Education, achieving an effectiveness score of 0.824911 or 82.49%, which falls into the high category. The Participatory Project-Based Learning Model (MP3) is an innovation derived from project-based learning, value-based learning, and service-learning models. Through this model, the local wisdom values embedded in Pilar Budaya Cianjur can be passed down with the aim of instilling these values in the younger generation.